CREATION OF A SUMMATION FORMULA MARSHALED WITH CONTIGUOUS RELATION AND HYPERGEOMETRIC FUNCTION (Global Journal of Science Frontier Research, 2011)
The main object of the present paper is to establish a summation formula tangled with Hypergeometric function and recurrence relation .
Keywords: Contiguous relation; Gauss second summation theorem; Re-currence relation